Publication of University of Idaho Ag News Releases by Idaho Daily and Weekly Newspapers in 1983 - Marlene Fritz (Journal of Applied Communications, 1985)
Publication of University of Idaho Ag News Releases by Idaho Daily and Weekly Newspapers in 1983